Root Cause Identification of Incomplete Medical Records Filing in Outpatient Clinic at Hospital X Malang City - Perdana, Yudha; Imam, Cecilia Widijati; Al Rasyid, Harun (Fakultas Kedokteran Universitas Brawijaya, 2024)
Completeness of medical records is one indicator of the quality of health services in hospitals. The completeness of medical records at X Hospital still does not meet the national standards that have been set. The purpose of this study was to identify the root cause of the incompleteness of the outpatient medical record document at Hospital X Malang City. This study used a descriptive research design by reviewing medical record documents and FGDs. Document review was conducted on 111 medical records taken by random sampling. Identification of the root of the problem is carried out through FGD activities by applying the 5 Why's. The results of the FGD showed that there were three factors that contributed to the incompleteness of medical records at X Hospital, namely humans, machines, and methods. The root of the problems identified were not having electronic medical records, the number of patients was not proportional to the allocation of time for doctor's services, medical and nursing assessment sheets were combined into 1 sheet, lack of knowledge of doctor assistants, and quality indicators and telemedicine SOPs that were still not differentiated from outpatient clinics.